ANALYSIS OF INCOME TAX REPORTING ARTICLE 21 IN PT PANDA INDONESIA IBE TULUNGAGUNG - Eni Widhajati (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2022)
Based on the law, tax is a people's contribution to the state treasury so that it can be forced, with no contra achievements or direct remuneration. Collection of taxes based on legal norms to cover the costs of producing collective goods and services with the aim of achieving the general welfare This study aims to analyze the calculation, deposit, and reporting of employee salaries at PT PANDA INDONESIA IBE whether the calculations are in accordance with applicable regulations. The method used in this research is descriptive qualitative, namely by analyzing the occurrence of miscalculation of taxes on employee salaries, as well as the treatment of status that affects the calculation of Article 21 Income Tax imposed on employees of PT PANDA INDONESIA. This study uses a qualitative descriptive method and design. In collecting data for this research through interview, observation, library research and documentation. The data analysis technique is done by grouping the data using the Triangulation Method which is done by comparing information or data in different ways. The results of the study can be concluded that in calculating and withholding the amount of income tax article 21 of 2018 and 2019 PT Panda Indonesia IBE has not been in accordance with the tax provisions applicable in that year in terms of the application of nontaxable income. This is because the company does not include overtime allowance of Rp. 143,000 in 2018 and Rp. 150,000 in 2019. Calculation and deduction of the amount of income tax article 21 of 2018 PT Panda Indonesia IBE in accordance with the tax provisions in force for that year. Because the company is already open, it means that all income from the President Director is included in the calculation of Article 21 Income Tax. In depositing and reporting the Article 21 Income Tax Return for 2018 – 2020 PT Panda Indonesia IBE has fulfilled its obligations properly and on time. In calculating PPh Article 21, it is advisable for the leadership of PT PANDA INDONESIA IBE to issue details of the calculation of PPh Article 21 to make it easier for each employee to know the detailed calculation of PPh Article 21. Keywords: tax, calculation, deposit and reporting of PPh Article 21